An improved method for calibrating time‐of‐flight Laue single‐crystal neutron diffractometers. (1st June 2014) - Bull, Craig L.; Johnson, Michael W.; Hamidov, Hayrullo; Komatsu, Kazuki; Guthrie, Malcolm; Gutmann, Matthias J.; Loveday, John S.; Nelmes, Richard J.
<x xml:space="preserve">Abstract</x> A robust and comprehensive method for determining the orientation matrix of a single‐crystal sample using the neutron Laue time‐of‐flight (TOF) technique is described. The new method enables the measurement of the unit‐cell parameters with an uncertainty in the range 0.015–0.06%, depending upon the crystal symmetry and the number of reflections measured. The improved technique also facilitates the location and integration of weak reflections, which are often more difficult to discern amongst the increased background at higher energies. The technique uses a mathematical model of the relative positions of all the detector pixels of the instrument, together with a methodology that establishes a reproducible reference frame and a method for determining the parameters of the instrument detector model. Since all neutron TOF instruments require precise detector calibration for their effective use, it is possible that the method described here may be of use on other instruments where the detector calibration cannot be determined by other means.